Mapping with ArcGIS Pro : Design accurate and user-friendly maps to share the story of your data. - Rock, Amy (Packt Publishing, 2018)
ArcGIS Pro is a geographic information system for working with maps and geographic information. Mapping with ArcGIS Pro will help readers create visually stunning maps that increase the legibility of the stories being mapped and introduce visual and design concepts into a traditionally scientific, data-driven process.